Triazolite, NaCu2(N3C2H2)2(NH3)2Cl3·4H2O, a new mineral species containing 1, 2, 4-triazolate anion, from a guano deposit at Pabellón de Pica, Iquique Province, Chile. (2nd August 2018) - Chukanov, Nikita V.; Zubkova, Natalia V.; Möhn, Gerhard; Pekov, Igor V.; Belakovskiy, Dmitriy I.; Van, Konstantin V.; Britvin, Sergey N.; Pushcharovsky, Dmitry Y.
ABSTRACT: The new mineral triazolite is found in a guano deposit located on the Pabellón de Pica Mountain, Iquique Province, Tarapacá Region, Chile. Associated minerals are salammoniac, halite, dittmarite, joanneumite, chanabayaite, nitratine, natroxalate and möhnite. Triazolite occurs as deep blue prismatic crystals up to 0.1 mm × 0.15 mm × 0.75 mm and their radial aggregates up to 1.5 mm across. The mineral is brittle. Its Mohs hardness is 2. D calc = 2.028 g cm –3 . The infrared spectrum shows the presence of 1, 2, 4-triazolate anion and ammonia and water molecules. Triazolite is optically biaxial (–), α = 1.582(4), β = 1.625(3), γ = 1.625(3) and 2Vmeas = 5(3)°. The chemical composition (electron-microprobe data for Cl, Na, Fe and Cu; H, C, N and S contents were measured by gas chromatography of products of ignition at 1200°C; wt.%) is: Na 4.91, Fe 1.51, Cu 22.06, Cl 19.80, S 1.4, C 7.7, H 4.4, N 24.2, O (calc.) 12.83, total 98.81. The empirical formula is Na1.14 (Cu1.86 Fe0.14 )(Cl2.99 S0.23 )N9.23 C3.43 H23.34 O4.29 . The idealized formula is NaCu2 (N3 C2 H2 )2 (NH3 )2 Cl3 ·4H2 O. Triazolite is a metalorganic ammine complex in which 1, 2, 4-triazolate anion and ammonia molecule are ligands coordinating Cu 2+ . The crystal structure was solved by direct methods and refined to R = 0.0242 based on 4210 unique reflections with I > 2σ( I ). Triazolite is orthorhombic, space group P 21 21 21, a = 19.3575(5), b = 7.15718(19), c = 12.5020(4) Å, V = 1732.09(8) Å 3 and Z = 4. The eight strongest reflections of the powder X-ray diffraction pattern [ d, Å ( I, %) ( hkl )] are: 10.22 (97) (101), 6.135 (40) (011), 5.696 (17) (301), 5.182 (59) (202), 5.119 (100) (211), 4.854 (19) (400), 3.752 (16) (312, 501), 3.294 (18) (221). Triazolite is named for the presence of 1, 2, 4-triazolate anion.